Interactive Learnıng Media Development Math Case Based on Scratch Triangle and Parallelogram Grade V Elementary School - Nabilah Az-zahrah; Sukriadi; Andi Asrafiani Arafah; Muhlis; Hety Diana Septika; Rosita Putri Rahmi (Jurnal Pendidikan Matematika (JPM), 2024)
The development of Scratch-based Math Case interactive learning media uses the Research & Development method which produces an interactive learning media that can be accessed without using an application. The aim of this study was to ascertain the developmental process, validity, and practicality of Scratch. This study employs the ADDIE development model, comprising 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The subjects of this study were students of class V-A at SDN 004 Samarinda Ulu and 1 teacher of class V-A. The result of this research is Scratch interactive learning media in the form of links that can be used without using the application. This media has been tested for validity and practicality by several experts and responses from research subjects. The validity assessment from linguists scored 86% in a very decent category, the validity assessment from material experts scored 84% in a very decent category, and the validity assessment from media experts scored 86% in a very decent category. Practicality assessment was carried out through small-scale and large-scale trials. The practicality of small-scale trials on students obtained an assessment of 83% with a very feasible category. The practicality of large-scale trials on students obtained an assessment of 87% with a very feasible category and the practicality of large-scale trials on educators obtained an assessment of 96% with a very feasible category. Based on these stages, this Scratch media can be used in the classroom as an interactive learning media.